Działania organizacji pozarządowych na rzecz wyrównywania szans edukacyjnych dzieci ze środowiska wiejskiego - Palka, Katarzyna (Karkonoska Państwowa Szkoła Wyższa, 2012)
We live in a world where the access to knowledge has a decisive influence on our future. A large number of children in Poland have difficulties with this access, because they are raised in impoverished, excluded, poorly educated families of low social status. This phenomenon is mainly related to rural areas. Nonformal education should provide important support for formal education. Nonformal education should be organized with the cooperation of schools, kindergartens, and non-governmental organizations. The educational activities proposed forchildren and their parents by non-governmental organizations complement formaleducation. These activities are of crucial importance in the equalization of educationalopportunities for children from rural areas. It is essential that these activities be planned, long-term, and a part of the entire educational program.
Keywords: dzieci; organizacje pozarządowe; edukacja; środowisko wiejskie